(untitled) (Journal of the College of Basic Education, 2022)
Nowadays the broadcast political interview plays such an important role in both the media and the political process that it has become the focus of present day research,(Cohen,1987:23).The most extensive work has been within the general framework of Conversation Analysis, and there is no doubt that this work has been fruitful (See Heritage,1985;